Financial Distress Analysis of Media Companies Listed on the IDX during the Covid-19 Pandemic - Meiliasari, Vika; Biyanto, Frasto; Siregar, Baldric; Miswanto, Miswanto (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This study focuses on assessing the risk of financial distress that may occur in media companies listed on the Indonesia Stock Exchange (IDX) during the Covid-19 pandemic period. The pandemic has significantly impacted various economic sectors, including the media sector, which faced severe pressure due to declining advertising revenues and shifts in consumer behavior towards digital platforms. The research employs a quantitative approach using the Altman Z-Score method to project the potential bankruptcy of companies. The data analyzed consists of financial reports from media companies listed on the IDX during the pre-pandemic and pandemic periods, specifically from 2020 to 2022. The analytical technique utilized in this study involves multiple regression analysis. The findings reveal that profitability, liquidity, and company size collectively influence financial distress. However, when analyzed individually, only liquidity has a positive impact on financial distress, while profitability and company size do not exhibit significant effects. These results are expected to provide insights into the financial conditions of media companies during the pandemic and identify factors contributing to the risk of financial distress. This information can serve as a guide for media company management, investors, and other stakeholders in developing strategies to mitigate bankruptcy risks in the future.